Protocol for an observational study investigating hormones triggering the onset of sustained lactation: the INSIGHT study. Issue 8 (30th August 2022) - Rostom, Hussam; Meng, Xin; Price, Helen; Fry, Alexandria; Elajnaf, Taha; Humphrey, Robert; Guha, Nishan; James, Tim; Kennedy, Stephen H; Hannan, Fadil M
Abstract : Introduction: Lactation is a hormonally controlled process that promotes infant growth and neurodevelopment and reduces the long-term maternal risk of diabetes, cardiovascular disease and breast cancer. Hormones, such as prolactin and progesterone, mediate mammary development during pregnancy and are critical for initiating copious milk secretion within 24–72 hours post partum. However, the hormone concentrations mediating lactation onset are ill defined. Methods and analysis: The primary objective of the investigating hormones triggering the onset of sustained lactation study is to establish reference intervals for the circulating hormone concentrations initiating postpartum milk secretion. The study will also assess how maternal factors such as parity, pregnancy comorbidities and complications during labour and delivery, which are known to delay lactation, may affect hormone concentrations. This single-centre observational study will recruit up to 1068 pregnant women over a 3-year period. A baseline blood sample will be obtained at 36 weeks' gestation. Participants will be monitored during postpartum days 1–4. Lactation onset will be reported using a validated breast fullness scale. Blood samples will be collected before and after a breastfeed on up to two occasions per day during postpartum days 1–4. Colostrum, milk and spot urine samples will be obtained on a single occasion. Serum hormone reference intervals will be calculated as mean±1.96 SD, with 90% CIs determined for the upper and lower reference limits. Differences in hormone values between healthy breastfeeding women and those at risk of delayed onset of lactation will be assessed by repeated measures two-way analysis of variance or a mixed linear model. Correlations between serum hormone concentrations and milk composition and volume will provide insights into the endocrine regulation of milk synthesis. Ethics and dissemination: Approval for this study had been granted by the East of England—Cambridgeshire and Hertfordshire Research Ethics Committee (REC No. 20/EE/0172), by the Health Research Authority (HRA), and by the Oxford University Hospitals National Health Service Foundation Trust. The findings will be published in high-ranking journals and presented at national and international conferences. Trial registration number: ISRCTN12667795 .